2009
DOI: 10.1378/chest.08-2988
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Right Ventricular Function and Functional Status 6 Months After Acute Submassive Pulmonary Embolism

Abstract: Six months after experiencing submassive PE, a significant proportion of patients had echocardiographic and functional evidence of pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
148
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(158 citation statements)
references
References 34 publications
(16 reference statements)
1
148
1
4
Order By: Relevance
“…21 In a separate study of 144 anticoagulated submassive PE patients, 27% of patients were found to have higher pulmonary pressures at the 6-month follow up than at the initial presentation. 36 As alluded to above, these physiologic findings may have functional consequences for patients, referred to by some as 'the post-PE syndrome'. 37,38 In one prospective cohort of 109 previously healthy patients who developed acute submassive PE, 41% displayed poor exercise tolerance (assessed using the 6-minute walk test or New York Heart Association (NYHA) status) or persistent RV dysfunction (by echocardiography) 6 months later.…”
Section: Question 3: Can Thrombolytic Therapy Improve Long-term Outcomentioning
confidence: 99%
“…21 In a separate study of 144 anticoagulated submassive PE patients, 27% of patients were found to have higher pulmonary pressures at the 6-month follow up than at the initial presentation. 36 As alluded to above, these physiologic findings may have functional consequences for patients, referred to by some as 'the post-PE syndrome'. 37,38 In one prospective cohort of 109 previously healthy patients who developed acute submassive PE, 41% displayed poor exercise tolerance (assessed using the 6-minute walk test or New York Heart Association (NYHA) status) or persistent RV dysfunction (by echocardiography) 6 months later.…”
Section: Question 3: Can Thrombolytic Therapy Improve Long-term Outcomentioning
confidence: 99%
“…In an analysis of normotensive PE patients (n = 162) treated with adjunctive fibrinolysis or heparin alone, no patients treated with fibrinolytics had an RV systolic pressure (RVSP) at 6 months' follow-up that was greater than that at diagnosis [35]. In contrast, 27 % of heparin-only patients had worsened RVSP at 6 months, 46 % of which had dyspnea with limited activity or at rest (New York Heart Association C3) or exercise intolerance (6-min walking distance\330 m) [35]. These findings suggest fibrinolysis may reduce the development of CTEPH.…”
Section: Quality Of Lifementioning
confidence: 99%
“…These findings suggest fibrinolysis may reduce the development of CTEPH. When the analysis was limited to those who had RVSP [30 mmHg at baseline, however, only 9 % of heparinmonotherapy patients had an RVSP increase at 6 months [35]. Table 3 also summarizes key safety results, including total major, intracranial, fatal, and minor bleedings, from randomized clinical trials evaluating the use of fibrinolysis in submassive PE.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Patients with severe tricuspid regurgitation, implying more severe PE and more hemolysis appear to be at the highest risk of acute L-arginine depletion, and persistent right ventricular dysfunction [6,7].…”
Section: Introductionmentioning
confidence: 99%